PREPARATION OF ACYCLOVIR-NICOTINAMIDE COCRYSTAL BY SOLVENT EVAPORATION TECHNIQUE WITH VARIATION OF SOLVENT - NAWATILA, ROISAH (2017)
Objective: This research aims to prepare cocrystal of acyclovir (ACV)-nicotinamide (NCT) by solvent evaporation with a variation of solvent (ethanol, glacial acetic acid, and HCl 0.1 N) to improve the bioavailability of ACV as an antiviral drug. Methods: Cocrystal were developed by solvent evaporation with 1:1 molar fraction, using variation of solvent such as ethanol, glacial acetic acid, and HCl 0.1 N. Further, the prepared ACV-NCT cocrystal were characterized for differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscope (SEM), and in vitro dissolution. Results: DSC thermogram showed that ACV-NCT cocrystal in ethanol and glacial acetic acid exhibited new endothermic peak at 221.16°C and 216.40°C, whereas no peaks were found for HCl 0.1 N. PXRD diffractogram showed that ACV-NCT cocrystal in ethanol exhibited new diffraction peaks at 2θ 5.9°; 9.2°; dan 13.3°, whereas no peaks were found for glacial acetic acid and HCl 0.1 N. FT-IR characterization of ACV-NCT cocrystal in ethanol showed disappearance of transmission peaks at 3373/cm indicating the loss of NH bands of NCT. Furthermore, C=O of ACV and NCT were observed at 1693/cm, and 1666/cm indicated a formation of hydrogen bonding between ACV and NCT. SEM micrographs showed that cocrystals have a different shape compared to ACV and NCT. DE showed that there was a significant increase of ACV-NCT cocrystal dissolution rate in ethanol compared to the physical mixture and ACV.